Deregulation of long noncoding RNA SNHG17 and TTC28-AS1 is associated with type 2 diabetes mellitus. (3rd October 2019) - Mohamadi, Mahroo; Ghaedi, Hamid; Kazerouni, Faranak; Erfanian Omidvar, Maryam; Kalbasi, Saeid; Shanaki, Mehrnoosh; Miraalamy, Ghasem; Rahimipour, Ali
Abstract: Long noncoding RNAs (lncRNAs) have emerged as key players in several biological processes and complex diseases including type 2 diabetes mellitus (T2DM). The purpose of this study was to investigate the expression levels of SNHG17 and TTC28-AS1 in T2DM patients. Quantitative real‐time RT‐PCR analysis was performed using peripheral blood mononuclear cells (PBMCs) samples from patients diagnosed with T2DM and healthy controls. Binary logistic regression analysis was carried out to determine the odds of development of T2DM based on expression levels of lncRNAs and clinical characteristic of the subjects. Spearman's correlation analysis was used to clarify the correlation between SNHG17 and TTC28-AS1 expressions to metabolic features. We found that SNHG17 and TTC28-AS1were down-regulated in the T2DM group compared to the healthy control group. The logistic regression revealed that body mass index (BMI), systolic blood pressure (SBP), fasting blood glucose (FBG) and TTC28-AS1 expression substantially affect T2DM susceptibility. Furthermore, expression of SNHG17 was negatively correlated with high‐density lipoprotein cholesterol (HDL‐C) and expression of TTC28-AS1 was positively correlated with low‐density lipoprotein cholesterol (LDL‐C). Decreased expressions of lncRNAs TTC28-AS1 and SNHG17 in T2DM are possibly associated with the development of T2DM.